Desain Mozaik Pada Interior Persegi Berkarakter Barisan Geometri - Murihani, Endang; Kusno, Kusno; Santoso, Kiswara Agung (Prosiding Seminar Matematika dan Pendidikan Matematik, 2014)
Mosaic is a creation that arranging pieces of geometric in a space. This mosaic design which has geometric line character enrich the varieties of mosaic designs more attractive and various. The result of research found that to develop the mosaic design in rectangle interior for geometric line character needed some steps as follows: (1) constructing pieces of rectangle that the size is arranged in geometric line form through spot among each side, (2) fill in each pieces in the result of step (1) with filling curve permanently or exchanging by using the rotation or dilatation, (3) combaining some rectangles as the result of step (2) and coloring the background or filling curve.